Nano-Hybrid Surface Coatings on Uncoated Papers from Softwood Fibers and Woodfree Fibers and Printability - (:unkn) unknown (ASIAN JOURNAL OF CHEMISTRY, 2011)
Nano-hybrid coatings are deposited as a top-coating onto various paper substrates from a stable dispersion with maximum solid content of 100 wt. %. The nano-hybrid coatings that blend of fluocarbon resin and polymers of highly branched dendrimers in a matrix of hydrocarbons was applied, on various basis of papers from consisting of both softwood fibers and woodfree fibers. Scanning electron microscopy images showed complete nanoparticle coating on these papers. The morphology, physical characteristics and chemical surface properties of the coatings are discussed using scanning electron microscopy. The thickness of the nano-hybrid coating was estimated as 2-3 mm for woodfree papers corresponds to average I % nanoparticle loading of the fibers. The basis weight of coated paper handsheets from woodfree fibers showed that nanoparticle coating gave handsheet weight higher than the weightness of the first papers. The paper handsheets prepared with nanoparticle-coated fibers had higher water resistance. Due to the high printing properties (flexo printing test and off-set printing test) and water repellence (reduction of Cobb-values), the interaction of the nanoparticle coatings with the woodfree paper results in improvement of the mechanical paper strength and is attributed to hydrogen-bonding between the nanoparticles and the cellulosic fibers.
Keywords: Nano-hybrid top-coating; Uncoated papers; Water resistance; Printability; Colour differences; BARRIER PROPERTIES; SILICA; COPOLYMER; PIGMENTS; LATICES